(untitled) (Research, Society and Development, 2024)
This article aims to analyze, in a panoramic way, the trajectory of educational policies for professional education in Brazil, as well as to point out the perspectives of this type of education in the State of Bahia. For that, we adopted as methodological procedures the qualitative research, of bibliographic and documentary character. Regarding the bibliographical review, we resorted to the studies by Azevedo (2004), Saviani (2007), Shiroma; Coan (2012), Castro (2020), among others; among the documentary sources, we used the Law of Guidelines and Bases of National Education, nº 9394/1996 and, at a regional level, the Guidelines for cost analysis in Professional Education (2012), Professional Education of Bahia and Identity Territories: volumes I (2012) and II (2014), Bahia Professional Education Forum Report (2011), Bahia State Professional Education Yearbook and Professional Education Booklet (2018), among others. By observing the analyzed aspects, we highlight the need for joint action by all segments of society in order to minimize the distance between legal provisions and everyday school life.